Establishment of knockout adult sea urchins by using a CRISPR‐Cas9 system. (29th July 2019) - Liu, Daming; Awazu, Akinori; Sakuma, Tetsushi; Yamamoto, Takashi; Sakamoto, Naoaki
Abstract: Sea urchins are used as a model organism for research on developmental biology and gene regulatory networks during early development. Gene knockdown by microinjection of morpholino antisense oligonucleotide (MASO) has been used to analyze gene function in early sea urchin embryos. However, as the effect of MASO is not long lasting, it is impossible to perturb genes expressed during late development by MASO. Recent advances in genome editing technologies have enabled gene modification in various organisms. We previously reported genome editing in the sea urchin Hemicentrotus pulcherrimus using zinc‐finger nuclease (ZFN) and transcription activator‐like effector nuclease (TALEN); however, the efficiencies of these technologies were not satisfactory. Here, we applied clustered regularly interspaced short palindromic repeat (CRISPR)‐CRISPR‐associated nuclease 9 (Cas9) technology to knock out the Pks1 gene in H. pulcherrimus . When sgRNAs targeting Pks1, which is required for the biosynthesis of larval pigment, were microinjected into fertilized eggs with SpCas9 mRNA, high‐efficiency mutagenesis was achieved within 24 hr post fertilization and SpCas9/sgRNA‐injected pluteus larvae had an albino phenotype. One of the sgRNAs yielded 100% mutagenesis efficiency, and no off‐target effect was detected. In addition, the albino phenotype was maintained in juvenile sea urchins after metamorphosis, and the knockout sea urchins survived for at least one year and grew to albino adult sea urchins. These findings suggest that knockout adult sea urchins were successfully established and the CRISPR‐Cas9 system is a feasible method for analyzing gene functions from late developmental to adult stage. Abstract : High‐efficiency mutagenesis was achieved by CRISPR‐Cas9 system in sea urchin, Hemicentrotus pulcherrimus . We targeted the pigmentation‐related HpPks1 gene, and knockout adult sea urchins were successfully established.